Comprehensive Evaluation of Lipid Nanoparticles and Polyplex Nanomicelles for Muscle-Targeted mRNA Delivery - Xuan Du; Erica Yada; Yuki Terai; Takuya Takahashi; Hideyuki Nakanishi; Hiroki Tanaka; Hidetaka Akita; Keiji Itaka (Pharmaceutics, 2023)
The growing significance of messenger RNA (mRNA) therapeutics in diverse medical applications, such as cancer, infectious diseases, and genetic disorders, highlighted the need for efficient and safe delivery systems. Lipid nanoparticles (LNPs) have shown great promise for mRNA delivery, but challenges such as toxicity and immunogenicity still remain to be addressed. In this study, we aimed to compare the performance of polyplex nanomicelles, our original cationic polymer-based carrier, and LNPs in various aspects, including delivery efficiency, organ toxicity, muscle damage, immune reaction, and pain. Our results showed that nanomicelles (PEG-PAsp(DET)) and LNPs (SM-102) exhibited distinct characteristics, with the former demonstrating relatively sustained protein production and reduced inflammation, making them suitable for therapeutic purposes. On the other hand, LNPs displayed desirable properties for vaccines, such as rapid mRNA expression and potent immune response. Taken together, these results suggest the different potentials of nanomicelles and LNPs, supporting further optimization of mRNA delivery systems tailored for specific purposes.